2018
DOI: 10.1021/acsami.8b01627
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Platform for Nanoparticle Surface Bioengineering Based on SiO2-Binding Peptide and Proteinaceous Barnase*Barstar Interface

Abstract: Nanoparticle surface engineering can change its chemical identity to enable surface coupling with functional biomolecules. However, common surface coupling methods such as physical adsorption or chemical conjugation often suffer from the low coupling yield, poorly controllable orientation of biomolecules, and steric hindrance during target binding. These issues limit the application scope of nanostructures for theranostics and personalized medicine. To address these shortfalls, we developed a rapid and versati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…This approach allows the robust self-assembly of multifunctional superstructures consisting of different singlefunction particles such as labels, carriers, recognition, and targeting agents, including antibodies. This bioengineering method employs two unique proteins from Bacillus amyloliquefaciens, barnase and barstar, to rapidly bring together the structural components directly in solution [137]. The properties of the superstructures can be designed on demand by linking different agents of various sizes and chemical nature, as a function of the specific purpose.…”
Section: Functionalization Of Nanoparticles By Biological Entitiesmentioning
confidence: 99%
“…This approach allows the robust self-assembly of multifunctional superstructures consisting of different singlefunction particles such as labels, carriers, recognition, and targeting agents, including antibodies. This bioengineering method employs two unique proteins from Bacillus amyloliquefaciens, barnase and barstar, to rapidly bring together the structural components directly in solution [137]. The properties of the superstructures can be designed on demand by linking different agents of various sizes and chemical nature, as a function of the specific purpose.…”
Section: Functionalization Of Nanoparticles By Biological Entitiesmentioning
confidence: 99%
“…In this platform technology, LPG acts as an anchor for the rapid and oriented immobilization of antibodies onto silica surfaces, thereby ensuring the functional display of conjugated antibodies without the need for complex conjugation chemistry. Although this linker technology has been widely used in several biotechnology and biomedical applications [14][15][16][17], there is still a lack of understanding about the interaction mechanism which facilitates the binding of this SBP to the silica surface.…”
Section: Introductionmentioning
confidence: 99%
“…The expression level of the tumor-associated HER- 2/neu antigen on the surface of the cultured cell lines was tested using fluorescence microscopy and the previously designed recombinant constructs for visualizing cancer cells expressing the HER-2/neu antigen (anti-HER2/neu mini-antibody-barstar●GFP-barnase) [36, 37]. It has been demonstrated that the cell culture samples being used are characterized by a sufficiently high level of expression of the HER-2/neu surface antigen (the data are not shown).…”
Section: Methodsmentioning
confidence: 99%